MEK inhibition suppresses metastatic progression of KRAS‐mutated gastric cancer. Issue 3 (7th January 2022) - Yamasaki, Juntaro; Hirata, Yuki; Otsuki, Yuji; Suina, Kentaro; Saito, Yoshiyuki; Masuda, Kenta; Okazaki, Shogo; Ishimoto, Takatsugu; Saya, Hideyuki; Nagano, Osamu
Abstract: Metastatic progression of tumors is driven by genetic alterations and tumor‐stroma interaction. To elucidate the mechanism underlying the oncogene‐induced gastric tumor progression, we have developed an organoid‐based model of gastric cancer from GAstric Neoplasia (GAN) mice, which express Wnt1 and the enzymes COX2 and microsomal prostaglandin E synthase 1 in the stomach. Both p53 knockout (GAN‐p53KO) organoids and KRAS G12V ‐expressing GAN‐p53KO (GAN‐KP) organoids were generated by genetic manipulation of GAN mouse‐derived tumor (GAN wild‐type [WT]) organoids. In contrast with GAN‐WT and GAN‐p53KO organoids, which manifested Wnt addiction, GAN‐KP organoids showed a Wnt‐independent phenotype and the ability to proliferate without formation of a Wnt‐regulated three‐dimensional epithelial architecture. After transplantation in syngeneic mouse stomach, GAN‐p53KO cells formed only small tumors, whereas GAN‐KP cells gave rise to invasive tumors associated with the development of hypoxia as well as to liver metastasis. Spatial transcriptomics analysis suggested that hypoxia signaling contributes to the metastatic progression of GAN‐KP tumors. In particular, such analysis identified a cluster of stromal cells located at the tumor invasive front that expressed genes related to hypoxia signaling, angiogenesis, and cell migration. These cells were also positive for phosphorylated extracellular signal‐regulated kinase (ERK), suggesting that mitogen‐activated protein kinase (MAPK) signaling promotes development of both tumor and microenvironment. The MEK (MAPK kinase) inhibitor trametinib suppressed the development of GAN‐KP gastric tumors, formation of a hypoxic microenvironment, tumor angiogenesis, and liver metastasis. Our findings therefore establish a rationale for application of trametinib to suppress metastatic progression of KRAS‐mutated gastric cancer. Abstract : Schematic representation of the phenotypic shift from Wnt addiction to Wnt independence of KRAS‐mutated tumor cells and hypoxia‐promoted metastasis.